2022
DOI: 10.3389/fphys.2022.933235
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting Breast Myopathies in Broiler Chickens and Quality of Defective Meat: A Meta-Analysis

Abstract: Fast-growing broiler chickens are subjected to breast myopathies such as white striping (WS), wooden breast (WB), and spaghetti meat (SM). Available studies about risk factors for myopathy occurrence often used flock data whereas a few reports evaluated chicken individual data. Thus, the present study aimed to elucidate the effect of growth and slaughter traits, besides sex and genotype on myopathy occurrence. Data were obtained from eight experimental trials, which used a total of 6,036 broiler chickens. Sex,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
12
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 78 publications
6
12
2
Order By: Relevance
“…According to Bailey et al (2020) , the heritability of myopathies is rather low (0.25 for WS and 0.07 for WB), whereas non-genetic factors are of greater importance in the development of defective meat. Thus, nor the present or previous studies ( Trocino et al, 2015 ; Bordignon et al, 2022 ) found relevant differences in WS occurrence among fast-growing genotypes. On the other hand, as for WB in males, Bordignon et al (2022) found that WB occurrence was significantly affected by genotype with large differences in the odds of having WB among 3 commercial genotypes.…”
Section: Discussioncontrasting
confidence: 96%
See 1 more Smart Citation
“…According to Bailey et al (2020) , the heritability of myopathies is rather low (0.25 for WS and 0.07 for WB), whereas non-genetic factors are of greater importance in the development of defective meat. Thus, nor the present or previous studies ( Trocino et al, 2015 ; Bordignon et al, 2022 ) found relevant differences in WS occurrence among fast-growing genotypes. On the other hand, as for WB in males, Bordignon et al (2022) found that WB occurrence was significantly affected by genotype with large differences in the odds of having WB among 3 commercial genotypes.…”
Section: Discussioncontrasting
confidence: 96%
“…The etiology of these muscle abnormalities has not been fully elucidated, although literature data imply that heritability has a negligible role ( Bailey et al, 2020 ) and environmental and/or management factors contribute more than 90% of the variance of WB occurrence and more than 65% of the variance of WS ( Bailey et al, 2015 ). Increased LW is a risk factor for both WB and WS occurrence ( Che et al, 2022 ), whereas the association between high-breast yield and WB and WS development has also been reported ( Lake et al, 2020 ; Bordignon et al, 2022 ). Some authors ( Trocino et al, 2015 ; Pascual et al, 2020 ) found that sex plays a role in the occurrence and severity of the different myopathies.…”
Section: Introductionmentioning
confidence: 99%
“…However, in contrast to the substantial improvement in growth rate and BW observed here, it should be noted that arginine supplementation tested in the studies just cited did not exert a positive effect on BW gain. Previous research has established that breast muscle abnormalities of fastgrowing, high meat-yielding broilers are deeply related to their extraordinary growth potential: the higher the growth performance, the greater the risk of myopathy onset [59][60][61]. It is therefore very likely that the significant arginine-mediated growth promotion exacerbated WS rather than the supplemental dietary arginine per se.…”
Section: Discussionmentioning
confidence: 99%
“…Through more than 70 years of intense genetic selection and effective nutritional programs, increased body weight, growth rates, and feed efficiency have been achieved among modern broiler chickens [ 14 ]. Genetic selection programs and nutritional programs have been designed to produce broilers with higher breast meat yields and body weight without considering fat accumulation, resulting in high levels of fat accumulation in modern broilers [ 15 , 16 , 17 , 18 ]. The increased production of breast meat has resulted in a decrease in leg meat production in modern broilers due to a change in body shape [ 19 ].…”
Section: Challenging Conditions In Broiler Production Are Associated ...mentioning
confidence: 99%